A peek at leaks and basement backups: a pilot survey exploring the impacts and outcomes of untreated sewage in homes - Maeghen Goode; John Junior Abu; Priscila B R Alves; Emily M H Woerner; Taeilorae Levell-Young; Taylor Smith-Hams; Alice Volpitta; Rita Crews; Malika Brown; Rachel E Rosenberg Goldstein; Marccus D Hendricks (Environmental Research Communications)
This study explores the outcomes and impacts of sanitary sewer overflows (SSOs) and basement backups in underserved communities in Baltimore, Maryland. The larger effort is an environmental and community-driven mixed-methods project, however, the research in this manuscript focuses on the household survey portion with residents who have experienced SSOs or sewage backups. Based on the snowball sampling method applied, the resulting residents engaged are predominantly African-American individuals, females, homeowners, and residents between the ages of 50 and 69. Strikingly, 70% of respondents reported that their frequency of SSOs is between moderate to frequent. The findings reveal that SSOs are a pervasive issue affecting residents’ physical and mental health and overall quality of life. Despite residents’ perceptions that their household infrastructure is in good condition, the recurring nature of SSOs highlights systemic problems within the city’s aging sewer systems, urging a deeper understanding of the social and structural vulnerabilities involved. This research calls attention to the importance of comprehensive interventions, including effective risk communication strategies and substantial investment in infrastructure rehabilitation, to mitigate the risks posed by SSOs and promote long-term resilience in urban environments. Additionally, it emphasizes the importance of community-driven research in addressing engineering, urban planning, and public health challenges with particular support for the most affected populations.